Improving Learning Outcomes through the Ular Tangga Raksasa Game on Civic Education in Elementary School - Suprianto, Oki; Ridwan, Ita Rustiati; Sundari, Nenden (Universitas Sebelas Maret, 2024)
This research is motivated by the low learning outcomes of students in civic education learning, namely 18 students with a percentage of 64.28% and only 10 students who completed their studies with a percentage of 45.71. This study aims to improve student learning outcomes in civic education learning in elementary schools through the ular tangga raksasa game. This research was conducted in class VB SDN Sempu 1 Serang City in the odd semester of the 2022/2023 academic year with 28 students. The PTK data collection technique used observation, interview, documentation and field notes. The research process was carried out according to the stages in classroom action research, namely starting with planning, implementation (action), observing and evaluating the process and results of the action (observation and evaluation), through reflection (reflection), then returning to the action planning stage until the desired learning quality is achieved. The results of the study showed an increase in student learning outcomes in Civic Education using the Giant Snakes and Ladders media, as evidenced by an increase in teacher activity, student activity and student learning outcomes in each cycle. The percentage of teacher activity in cycle I was 75%, cycle II was 87.50%, and cycle III was 94.44%. The percentage of student activity in cycle I was 72.22%, cycle II was 86.11%, and cycle III was 91.66%. The percentage of student learning outcomes completion in the pre-cycle was 35.71%, cycle I was 57.14%, cycle II was 75%, and cycle III increased with very good criteria of 89.28%. Based on the data that has been obtained, the researcher's objective in using the Giant Snakes and Ladders media in improving student learning outcomes in the subject of Civic Education has proven to be successful